Antibacterial, Antioxidant And Anti-Inflammatory Studies Of Lygodium Microphyllum - Ahmad, Radiah (2019)
Lygodium microphyllum is a fern which has been used traditionally for controlling dysentery, treating swellings and skin diseases, curing hiccups as well as controlling high fever and typhoid fever. The aim of the study was to evaluate the antibacterial, antioxidant and anti-inflammatory activities of five solvent fractions obtained from crude methanol extract of L. microphyllum leaves by liquid-liquid extraction of hexane, chloroform, ethyl acetate, n-butanol and water. Phytochemical analysis via Folin-Ciocalteu's method and aluminium chloride colorimetric method showed that ethyl acetate fraction obtained the highest total phenolic content of 11.59 ± 1.02 mg gallic acid equivalents (GAE)/g sample, whereas hexane fraction displayed the highest total flavonoid content of 60.27 ± 3.53 mg quercetin equivalents (QE)/g sample.